Genome-Wide Transcriptional Response of Mycobacterium smegmatis MC2155 to G-Quadruplex Ligands BRACO-19 and TMPyP4 - Shitikov, Egor; Bespiatykh, Dmitry; Malakhova, Maja; Bespyatykh, Julia; Bodoev, Ivan; Vedekhina, Tatiana; Zaychikova, Marina; Veselovsky, Vladimir; Klimina, Ksenia; Ilina, Elena; Varizhuk, Anna (Frontiers in Microbiology, 2022)
G-quadruplexes (G4s) are non-canonical DNA structures that could be considered as potential therapeutic targets for antimicrobial compounds, also known as G4-stabilizing ligands. While some of these ligands are shown in vitro to have a stabilizing effect, the precise mechanism of antibacterial action has not been fully investigated. Here, we employed genome-wide RNA-sequencing to analyze the response of Mycobacterium smegmatis to inhibitory concentrations of BRACO-19 and TMPyP4 G4 ligands. The expression profile changed (FDR < 0.05, log2FC > |1|) for 822 (515↑; 307↓) genes in M. smegmatis in response to BRACO-19 and for 680 (339↑; 341↓) genes in response to TMPyP4. However, the analysis revealed no significant ligand-induced changes in expression levels of G4-harboring genes, genes under G4-harboring promoters, or intergenic regions located on mRNA-like or template strands. Meanwhile, for the BRACO-19 ligand we found significant changes in the replication and repair system genes, as well as in iron metabolism genes which is, undoubtedly, evidence of the induced stress. For the TMPyP4 compound, substantial changes were found in transcription factors and the arginine biosynthesis system, which may indicate multiple biological targets for this compound.